The application of benthic diatoms in water quality assessment (Mlava River, Serbia) - Jakovljevic, Olga; Popovic, Sladana S.; Vidakovic, Danijela P.; Stojanovic, Katarina Z.; Krizmanic, Jelena Z. (Acta Botanica Croatica, 2016)
The main objective of this study was to assess the ecological status of the Mlava River based on epilithic diatoms and to test the use of diatom indices as a tool for estimating the quality of flowing waters in Serbia. Quantitative analysis showed that in April Achnanthidium minutissimum was dominant at each site, except at the fifth site, where Amphora pediculus was dominant. In July and September, Achnanthidium minutissimum, Achnanthidium pyrenaicum, Amphora pediculus, Denticula tenuis, Diatoma vulgaris, Gomphonema elegantissimum, Cocconeis pseudolineata and Cocconeis placentula var. lineata dominated. Detrended correspondence analysis (DCA) was used to detect the major patterns of variation in species composition. The first DCA axis summarizes the distribution of the diatom community, mainly through temperature, conductivity, oxygen and water hardness gradient. The second DCA axis was weakly correlated with few variables. Based on the average values of the pollution sensitivity index (IPS), commission for economical community metric (CEE) and biological diatom index (IBD), the water of the Mlava River belonged to water class I during all three seasons. Values of the diatom-based eutrophication/pollution index (EPI-D) indicated class II water quality. According to calculated trophic diatom index (TDI) values, water of the Mlava River was characterized by intermediate nutrient concentrations during three seasons. Principal components analysis was used to represent the correlation between diatom indices, and the highest correlation among the selected diatom indices is seen between EPI-D, IPS and IBD.